Financing of physical rehabilitation services in Iran: a stakeholder and social network analysis - Saeed Shahabi; Ahmad Ahmadi Teymourlouy; Hosein Shabaninejad; Mohammad Kamali; Kamran Bagheri Lankarani (BMC, 2020)
Abstract Background Inadequate financing is one of the major barriers in securing equitable access to high-quality physical rehabilitation services, without imposing financial hardship. Despite this, no sufficient attention has been paid to physical rehabilitation services and no specific financial resources have been allocated to such services in many countries including Iran. Owing to the fact that effective decision- and policy-making requires identifying possible stakeholders and actors and their characteristics, in the current study a stakeholder analysis and also a social network analysis (SNA) was conducted to identify the potential stakeholders and also their characteristics involved in physical rehabilitation financing (PRF)-related policies in Iran. Methods The present study was performed in two phases. Firstly, semi-structured interviews and relevant document review were conducted to identify the stakeholders. Then, the position, power, interest, and influence of each stakeholder were determined using a web-based questionnaire. Secondly, SNA approach was utilized to map and visualize the interactions among stakeholders. Results The findings showed that there are different stakeholders in PRF-related decision- and policy-making processes in Iran. In addition, the position, power, interest, and influence level of the identified stakeholders were varied. Moreover, although some stakeholders, like the Ministry of Health and the parliament have the highest level of power and position, they lack sufficient interest to participate in PRF-policies. Furthermore, SNA demonstrated that social network density was low, which indicates the lack of proper collaboration and interaction among the stakeholders. Conclusion As many powerful and influential stakeholders had low interest levels to warrant participate in the FPR-related decision- and policy-making processes in Iran, employing careful and effective strategies, that is ongoing negotiations, receiving advocacy, and making senior managers and policy-makers aware can be helpful.